PENGARUH KUALITAS AKTIVA PRODUKTIF DAN NON PERFORMING LOAN TERHADAP TINGKAT PROFITABILITAS PADA PT BPR KENCANA GRAHA - Agustina Agustina; Argo Putra Prima (Yayasan Azam Kemajuan Rantau Anak Bengkalis, 2020)
Bank itself collects public funds, is managed and distributed in the form of business capital loans or consumptive loans to the public. Credit is the main business, the data used are secondary data obtained from financial statements. The analytical method used is the classic assumption test, multiple linear regression, t test, f test and the coefficient of determination. Referring to the results of the analysis partially or t test significance level of 5% so that the results of this test conclude: (1) earning asset quality affects the profitability level known t value of 4,934 > t table 2,03224 with a significance value of 0,000 > 0,05, (2) non performing loans affect the profitability when t arithmetic of -9,732 > t table 2,03224 with a significance value of 0,000 > 0,05. And the f test results where earning asset quality and non-performing loans simultaneously influence the profitability of the calculated F value of 69,425 > F table 3,28 with a significance value of 0,000 < 0,05. The coefficient of determination (R2) of 0,803 or 80,3% of the quality of earning assets and non-perfoming loans affects profitability at PT BPR Kencana Graha, so the remaining 19,7% is influenced by other ratio factors.